Analysis of program outcomes attainment for diploma in civil engineering at Universiti Teknologi MARA Pahang - Nur Asmaliza Mohd Noor; Noor Safwan Muhamad; Rohaya Alias; Asmidar Alias; Siti Hawa Rosli (Institute of Advanced Engineering and Science, 2024)
Analysis of program outcomes involves the assessment of the learning objectives based on cognitive, psychomotor, and affective domains and their attainment is measured using both direct and indirect approaches. This study aims to assess the program outcomes attainment for the civil engineering diploma program at Universiti Teknologi MARA Pahang. The program outcomes attainment in this study was obtained from two categories of students based on cohort 20174 using the Plan ID 6541, namely i) 257 graduated on-time students and ii) 365 overall students including extended students. The attainments were analyzed quantitatively using key performance indicators for each program outcome and program performance indicators for the overall attainment of program outcomes. Based on the key performance indicator, the results reveal that nine program outcomes are indicated as excellent while three program outcomes are indicated as good. Meanwhile, based on the program performance indicator, this cohort is indicated as well performed where 9 out of 12 program outcomes recorded above 70% average attainment. Various effective continuous quality improvement (CQI) program can be identified by the school’s committee based on these findings to further enhance the program outcomes attainment.